Sanctions and tourist flows: The roles of religion and geography - Usman Khalid; Luke Emeka Okafor; Katarzyna Burzynska (Annals of Tourism Research Empirical Insights, 2024)
This study explores whether different types of sanctions, such as arms, military, trade, finance, and travel sanctions, affect bilateral tourist flows from the sender to the sanctioned country. It also investigates the moderating roles of religious and geographical proximity on the underlying relationships. We use a panel gravity data set consisting of 206 origin countries, 189 destination countries, and 16,557 country-pairs over the period 1995 to 2018 for the empirical analysis. The results indicate that sanctions adversely impact bilateral tourist flows from the sender to the sanctioned country regardless of the type of sanction. The results also suggest that the negative effects of sanctions on bilateral tourist flows can be attenuated, to some extent, by geographical proximity and common religion.
Keywords: 330; Bilateral tourist flows; Common religion; Geographical proximity; Gravity model; Sanctions